Implementation of Problem Based Learning Model in Improving Al-Quran Reading and Writing Skills at SD Bintang Sergai - Rahayu, Syudiyah; Sitepu, Sri Rezeki; Putri, Hairani Ananda (MANDAILING GLOBAL EDUKASIA, 2024)
This study aims to improve students' ability to read and write the Quran in Islamic religious education learning by using Problem based learning model. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were elementary school students. The data for this study were obtained by test and observation techniques. The test was used to measure the ability to improve the ability to read and write the Quran and observation was used to analyze the learning activities of teachers and students. The data analysis technique used in this study was descriptive statistics by comparing the results obtained with indicators of research success. The results showed that Problem based learning model can improve students' ability to read and write the Quran in Islamic religious education learning. This can be seen from the increase in the percentage of student ability completion in each cycle with details of the pre-cycle 45.56%, the first cycle 68.47% and in the second cycle increased to 89.57%. Thus, the use of Problem based learning model can be used as an alternative to improve student learning outcomes in Islamic religious education learning.